Apert's syndrome: A rare craniofacial disorder - Prajakta C Khelkar; Aaditi N Kadam; Freny R Karjodkar; Kaustubh P Sansare (Wolters Kluwer Medknow Publications, 2020)
Apert's syndrome (AS) which is a rare congenital disorder is a form of acrocephalosyndactyly. This syndrome is characterized by craniosynostosis, midface hypoplasia, and syndactyly of hands and feet. We report a case of 13-year-old boy in India presenting features of AS such as exophthalmos, hypertelorism, strabismus, steep forehead, parrot beak nose, depressed nasal bridge, and retruded middle third of the face. The purpose of this report is to present a case of AS by highlighting the craniofacial characteristics.